1995
DOI: 10.3354/dao021069
|View full text |Cite
|
Sign up to set email alerts
|

A non-occluded, systemic baculovirus that occurs in cells of ectodermal and mesodermal origin and causes high mortality in the black tiger prawn Penaeus monodon

Abstract: for virus isolation and purification, 1 batch of prawns yielded hemolymph fractions dominated by a previously undescribed non-occluded baculovirus rather than YHV. Injection of test shrimp with a semipurified preparation of this virus gave rapid mortality, and examination with the transmission electron microscope revealed a dual infection where cells containing the new virus dominated, but some cells containing YHV could also be seen. The tissues infected by the 2 viruses were similar. However, in contrast to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
277
1
3

Year Published

2000
2000
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 399 publications
(287 citation statements)
references
References 3 publications
6
277
1
3
Order By: Relevance
“…Electron microscopic analysis showed that WSSV consists of a rod-shaped nucleocapsid with a cross-hatched appearance, surrounded by a trilaminar envelope with a unique tail-like appendix at one end (Wongteerasupaya et al, 1995;Durand et al, 1997;. The circular dsDNA genome of WSSV has a size of around 300 kb and is one of the largest animal virus genomes that has been entirely sequenced (van Hulten et al, 2001;Yang et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Electron microscopic analysis showed that WSSV consists of a rod-shaped nucleocapsid with a cross-hatched appearance, surrounded by a trilaminar envelope with a unique tail-like appendix at one end (Wongteerasupaya et al, 1995;Durand et al, 1997;. The circular dsDNA genome of WSSV has a size of around 300 kb and is one of the largest animal virus genomes that has been entirely sequenced (van Hulten et al, 2001;Yang et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…By 1995 WSS virus (WSSV) outbreaks in shrimp culture facilities had been reported in Japan, Korea, Thailand, Taiwan, Indonesia and India affecting farmed populations of P. chinensis, P. monodon, P. japonicus and P. indicus , Winaro 1995, Wongteerasupaya et al 1995, Heo et al 1998, Mohan et al 1998. Partly because of the rapid spread of the virus and its identification by numerous laboratories, the virus has been referred to by various other names including rod-shaped nuclear virus of P. japonicus , systemic ectodermal and mesodermal baculovirus (Wongteerasupaya et al 1995), hypodermal and hematopoietic necrosis baculovirus , white spot baculovirus , Chinese baculovirus (Nadala et al 1997) and P. monodon non-occluded baculovirus . Very rapidly, WSSV spread to other regions of the world.…”
Section: Introductionmentioning
confidence: 99%
“…1995). WSSV is an enveloped virus with a large, double-stranded, circular DNA genome (∼300 kb) containing approximately 180 putative open reading frames (ORFs), most of which have no homology with any known genes or proteins in public databases Wongteerasupaya et al 1995;Wang et al 1995;Chang et al 1996;Chen et al 1997;Yang et al 2001). Proper husbandry and management of farms with the application of immunostimulants, probiotics and bioremediators can save the industry from the onslaught of diseases to a certain extent.…”
Section: Introductionmentioning
confidence: 99%